From theory to practice: A bibliometric review of AI applications in management sciences - NEFFAH, Zakarya; Mokhtar, Idrissi; HABBAB, Ahmed (The International tax journal, 2026)
This study seeks to conduct a bibliometric analysis of the scientific literature that is concerned with using artificial intelligence in management, where the study try to treat dilemmas that rely on discovering the prevailing research trends within the field of using artificial intelligence as a helping tool for improving management processes through a bibliometric study. The study conclude the domination of Artificial Intelligence, the emerging importance of big data, and electronic commerce reflect the developing nature of research in response to technological advancements. As well as recommended that future research should aim to address gaps in the literature and foster interdisciplinary collaboration to drive innovation and knowledge creation.